Factors Causing Academic Cheating Behavior in the online system : A Systematic Literature Review - Kharisma Endarty; Aristanti Widyaningsih; Meta Arief (JEKAMI Journal of Accounting, 2024)
Academic cheating is a pervasive issue among students in higher education, particularly in the context of online learning. This study conducts a systematic literature review to examine the factors contributing to academic cheating in online systems, analyzing 24 journal articles published between 2019 and 2023. The research identifies key factors influencing academic dishonesty, including pressure, opportunity, rationalization, ability, arrogance, greed, need, disclosure, personal ethics, self-efficacy, and learning readiness. Among these, pressure and opportunity are the most significant, with 17 articles highlighting their impact. The findings suggest that frequent engagement in academic fraud can enhance students' ability to commit further dishonest acts, exacerbating the prevalence of academic fraud in universities. The study also explores the theoretical frameworks of fraud, such as the Pentagon Theory, which includes components like pressure, opportunity, rationalization, ability, and hubris, and the Gone Theory, focusing on greed, opportunity, need, and exposure. Methodologically, most research on this topic employs quantitative approaches, indicating a gap for qualitative studies. The study concludes that external academic activities, time management challenges, and a lack of preparedness contribute to students resorting to cheating as a shortcut. Recommendations emphasize integrating hard and soft skills in education, fostering teamwork, and encouraging active participation in discussions to mitigate academic dishonesty. Implementing objective evaluations and adhering to established policies can also help address this issue. Overall, the study underscores the complexity of academic cheating and the need for comprehensive strategies to reduce its occurrence in online learning environments.